The Effect of Technology Awareness and Government Support on the Acceptance of Identitas Kependudukan Digital Apps in Sumedang Using TAM Framework - Ruri Anggraeni; Franciskus Antonius Alijoyo (Riviera Publishing, 2025)
The acceptance of digital identity applications is crucial for the digitalization of public services in Sumedang Regency. Despite advancements, there remains a significant gap in understanding the factors influencing public acceptance of these applications. This study analyzes how external factors, specifically technology awareness and government support, impact the perceived usefulness and Ease of use of digital identity applications employing the technology acceptance model (TAM). Data were collected from 315 respondents across the Sumedang Regency using a quantitative survey method. The analysis reveals that Technology Awareness and Government Support significantly enhance Perceived Ease of Use and Usefulness. Notably, this research uncovers new findings indicating that enhanced government socialization efforts directly correlate with increased public acceptance. The study concludes with recommendations for local governments to improve socialization strategies, policy support, and application process simplification to foster greater acceptance of digital identity applications.